If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 12 = 3x + 2 Reorder the terms: 12 + x = 3x + 2 Reorder the terms: 12 + x = 2 + 3x Solving 12 + x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + x + -3x = 2 + 3x + -3x Combine like terms: x + -3x = -2x 12 + -2x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -2x = 2 + 0 12 + -2x = 2 Add '-12' to each side of the equation. 12 + -12 + -2x = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 2 + -12 -2x = 2 + -12 Combine like terms: 2 + -12 = -10 -2x = -10 Divide each side by '-2'. x = 5 Simplifying x = 5
| 99/3366 | | 2x+1+x=3(x-2)+7 | | 600=5x+10y | | (y-8)=2-4y | | 10x-5x-3=0 | | 5/6x-2/3=-4 | | x^4-12x^3+20x^2=0 | | 8x+2=3x+57 | | 3x+1=3(x-2)+7 | | 600= | | 7p^2+30p+8=0 | | 3n+11n=126 | | (3x-2)/8+(2-x)/4=-1/2 | | 2x^2+36=17x | | -2x+6-1.5x=1 | | -3x-2y=-7 | | x+y=2.5 | | x/16=-26 | | -9x+8y=8 | | 5x/8-2=15 | | 9=3(15-3x) | | 64-16t^2=0 | | 1.5f-2=1.6f | | 5(v-4)=2v-5 | | 12=3x-6y | | -16t^2+32=0 | | 9=3(15-3) | | 3x-6=0.5(4x+8) | | 8x+4y=-12 | | 0.6(25x+10)=6x+15 | | 4k+9=2k+15 | | 38782.13+0.1575y=y |